Pengaruh Pendidikan Kewirausahaan Terhadap Pengembangan Ide Bisnis Mahasiswa: The Influence of Entrepreneurship Education on Students' Business Idea Development - Simanjuntak, Yizreel; Nurdianti, Raden Roro Suci; Gumilar, Rendra (PUSDATIN Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2025)
The underlying issue addressed in this study is the difficulty students face in developing business ideas, which is attributed to a lack of skills acquired through entrepreneurship courses and practical training. This study aims to determine the influence of entrepreneurship education on business idea development among Class of 2023 students in the Department of Economic Education at Siliwangi University, Tasikmalaya. This study employed a survey method with a quantitative approach. The sampling technique used was non-probability sampling, specifically saturation sampling, involving a total of 138 respondents. Data were collected using questionnaires, and the data analysis technique employed was simple linear regression analysis. The results of the simple linear regression test yielded the equation Y=55.412+0.621X. With a significance value (Sig.) of 0.000, which is less than 0.05, the findings indicate a positive and significant influence of entrepreneurship education on the business idea development of Class of 2023 students in the Department of Economic Education at Siliwangi University, Tasikmalaya.